Developing Online Learning Assessment Instrument for English Sentence Structure Course during Covid-19 Pandemic - Emy Sudarwati; Fatimah Fatimah; Yuni Astuti; M. Faruq Ubaidillah (Institut Agama Islam Negeri (IAIN) Kendari, 2021)
Anchored by the need for constructing an online assessment which is mediated by honesty as the character value for grammar mastery among undergraduate students during Covid-19 pandemic, in the present study we developed a test of English Sentence Structure (ESS) situated in an English department of a public university in Malang, East Java, Indonesia. To enact such a purpose, Design-based Research (DBR) was carried out in the study. Findings from the study showcase that the test was valid and reliable, giving it accessible portion for use in the English department. Aside from that, students also opined positively toward the use of the test in measuring their English grammar mastery. Despite these, we found that students’ score in the tryout phase is low affected by their lack of test preparation, inappropriate situated test time, and ineffective teaching and learning enactment. The paper ends with recommendation for future researchers.